(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The purpose of the article is to study the growing role of Iran in Eurasian transport and communication initiatives. Due to its advantageous geopolitical and geo-economic positionIran is seen as an interesting partner for Russia, China and Central Asian countries. In thecon text of the transformation of the world order the Iranian leadership seeks to play a moresignificant role in regional economic and political processes, relying on its transport and transit potential. It is proved that Iran positions itself as a leading transport and logistics hub in Eurasia.
Keywords: russia; transit potential; transport; logistics; the Belt and Road initiative; Central Asia